Pendidikan Karakter Berbasis Budaya Pada Siswa SD Muhammadiyah di Kota Semarang - Masrukhi, Masrukhi; Supriyanto, Supriyanto; Anjar Setiawan (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
This research examines a culture-based character education model. This research method uses a qualitative approach. The research location is in the city of Semarang. The research objects at SD Muhammadiyah Semarang City were 16 schools. The research subjects were school principals, deputy principals and religious teachers. The research results are as follows; 1) involvement of parents in implementing culture-based character education. 2) Increase teacher discipline in providing examples for students in implementing culture-based character education. 3) Infrastructure support is needed to maximize culture-based character education such as. 4) Increased student discipline in the school environment. 5) There are meeting facilities between teachers and parents of students.